The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1027/2512-8442/a000086
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the PERMA Model as a Framework for Reducing Psychiatric Comorbidity in Individuals With Alopecia Areata

Abstract: Abstract. Background: Alopecia areata (AA) is among the most common immunological conditions. Although AA is considered to be a medically benign condition, those living with AA often report comorbid psychiatric conditions, high levels of functional impairment, and diminished quality of life. These consequences are largely due to the unique psychological turmoil associated with the condition. Unfortunately, little research has considered how to improve quality of life outcomes for this group. Aims: The purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…Social integration and support are well-documented as valuable coping strategies for individuals experiencing almost any type of health challenge (Tay et al, 2013). This held true in the present study and is consistent with previous findings on the AA experience (e.g., Barkauskaite & Serapinas, 2020; Huck et al., 2021). Unsurprisingly, this was the largest subcategory in the present study.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Social integration and support are well-documented as valuable coping strategies for individuals experiencing almost any type of health challenge (Tay et al, 2013). This held true in the present study and is consistent with previous findings on the AA experience (e.g., Barkauskaite & Serapinas, 2020; Huck et al., 2021). Unsurprisingly, this was the largest subcategory in the present study.…”
Section: Discussionsupporting
confidence: 94%
“…Matzer et al (2011) found evidence that people with AA are more prone to maladaptive coping strategies than the general population. Most recently, Huck et al (2021) applied the PERMA framework (Seligman, 2011) to evaluate associations between the PERMA elements (i.e., positive emotions, engagement, relationships, meaning, and achievement) and AA-related QOL, finding that the model held promise for understanding and supporting individuals.…”
Section: Coping With Alopecia Areatamentioning
confidence: 99%
“…Health-related quality of life was measured using the Patient-Reported Outcomes Measurement Information System (PROMIS ® ) global mental and physical health items, which were categorized by Hays et al (2009). The PROMIS global mental health and physical health scales consist of four items (e.g., “In general, would you say your quality of life is .…”
Section: Methodsmentioning
confidence: 99%
“…PERMA was built upon Authentic Happiness Theory (AHT; Seligman, 2002) to recognize the multidimensionality of well-being. PERMA has been examined in the field of rehabilitation (e.g., Huck et al, 2022;Tansey et al, 2018;Umucu, 2021). Seligman (2011aSeligman ( , 2011b stated that the purpose of well-being theory is to increase flourishing by increasing positive emotion, engagement, relationships, meaning, and accomplishment (i.e., PERMA).…”
Section: A Proposed Model For Well-being Contributing To College Adju...mentioning
confidence: 99%
“…Emphasizing positive psychological traits to promote happiness in individuals with disabilities can further benefit rehabilitation research, clinical practice, and consumer experiences (Chou et al, 2013; Dunn & Dougherty, 2005). Therefore, rehabilitation researchers and practitioners have been advocating for a paradigm shift from examining deficits in disability to focusing on positive psychosocial factors, including happiness (Chou et al, 2013; Dunn & Dougherty, 2005; Dunn et al, 2009; Fortuna et al, 2020; Huck et al, 2022; Grenawalt et al, 2022; Lee, 2022; Lee, Rumrill, et al, 2022; Lee, Rumril, Tansey, 2022; Moser et al, 2020; Phillips et al, 2022; Sánchez et al, 2019; Umucu, Lee, Berwick, et al, 2022; Umucu, Reyes, Carrola, et al, 2021; Umucu, Tansey, et al, 2021; Umucu, Wu, et al, 2020).…”
mentioning
confidence: 99%